Application of partial strength connection in the design of multi-storey braced steel frame using trapezoidal web profiled section - Md. Tahir, Mahmood; Tan, Cher Siang; Thong, Chin Mun (Faculty of Civil Engineering, UTM, 2005)
Eurocode 3 offers the opportunity to design steel frames as 'semi-continuous' by including the moment resistance of 'partial strength' connections in plastic hinge analysis of the frame. Semi-continuous construction with partial strength connections offers many benefits for braced frames such as shallower and lighter beams, standardized connections with less complicated geometry, and more robust frames than simple construction. It is expected to give significant savings in frame weight. This paper presents findings on a series of two-bay, four-bay and six-bay braced frames of two-, four-, six- and eight-storey with span ranging from 6 m to 9 m by comparing between Hot-rolled (HR) steel beams designed using simple construction and Trapezoidal Web Profiled (TWP) steel beams designed using the semi-continuous construction method. Flush end-plate and extended end-plate connections were used as partial strength joints whereas for the simple construction, partial depth flexible end-plate connections were used as pin joints. The semi-continuous design method can reduce the frame weight between 13.4% and 20.5% compared to simple construction.